New records of Cretaceous snakes in Argentina (Allen Formation, Río Negro Province) - Albino, Adriana María (2010)
Some of the most relevant fossil snakes that inform about the evolution and early diversity of the group, come from Cretaceous sediments of Argentina. Among them, the remains assigned to the extinct family Madtsoiidae have been found in Upper Cretaceous localities of northern Patagonia and consist in isolated and fragmentary vertebrae. In this contribution, new remains from the upper Campanian-lower Maastrichtian of the Allen Formation (Malargüe Group) are preliminarly described. They were collected in diverse localities of the centre Río Negro Province. Fragmentary vertebrae assignable to known genera (e.g., Alamitophis Albino), as well as others that probably belong to new taxa, have been found. Although craniomandibular elements are not frequent in Cretaceous deposits, a robust and relatively large left maxilla of a probable madtsoiid has also been recognized. These findings document the abundance and diversity of madtsoiids in the Upper Cretaceous of Patagonia and reinforce the similarities reported among Allen, Los Alamitos and La Colonia Formations